Characterization of bacteria expectorated during forced salivation of the Phlebotomus papatasi: A neglected component of sand fly infectious inoculums. - Naseh Maleki-Ravasan; Seyedeh Maryam Ghafari; Narmin Najafzadeh; Fateh Karimian; Fatemeh Darzi; Roshanak Davoudian; Reza Farshbaf Pourabad; Parviz Parvizi (Public Library of Science (PLoS), 2024)
The infectious inoculum of a sand fly, apart from its metacyclic promastigotes, is composed of factors derived from both the parasite and the vector. Vector-derived factors, including salivary proteins and the gut microbiota, are essential for the establishment and enhancement of infection. However, the type and the number of bacteria egested during salivation is unclear. In the present study, sand flies of Phlebotomus papatasi were gathered from three locations in hyperendemic focus of zoonotic cutaneous leishmaniasis (ZCL) in Isfahan Province, Iran. By using the forced salivation assay and targeting the 16S rRNA barcode gene, egested bacteria were characterized in 99 (44%) out of 224 sand flies. Culture-dependent and culture-independent methods identified the members of Enterobacter cloacae and Spiroplasma species as dominant taxa, respectively. Ten top genera of Spiroplasma, Ralstonia, Acinetobacter, Reyranella, Undibacterium, Bryobacter, Corynebacterium, Cutibacterium, Psychrobacter, and Wolbachia constituted >80% of the saliva microbiome. Phylogenetic analysis displayed the presence of only one bacterial species for the Spiroplasma, Ralstonia, Reyranella, Bryobacter and Wolbachia, two distinct species for Cutibacterium, three for Undibacterium and Psychrobacter, 16 for Acinetobacter, and 27 for Corynebacterium, in the saliva. The abundance of microbes in P. papatasi saliva was determined by incorporating the data on the read counts and the copy number of 16S rRNA gene, about 9,000 bacterial cells, per sand fly. Both microbiological and metagenomic data indicate that bacteria are constant companions of Leishmania, from the intestine of the vector to the vertebrate host. This is the first forced salivation experiment in a sand fly, addressing key questions on infectious bite and competent vectors.